Strongly almost summable sequences of order ? - Et, Mikail; Colak, Rifat; Altin, Yavuz (Academic Publication Council, 2014)
In this paper, we introduce the concept (S) over cap (alpha)(lambda)-statistical convergence of order a. Also some relations between (S) over cap (alpha)(lambda)-statistical convergence of order a and strong (w) over cap (beta)(p)(mu) - summability of order beta are given. Furthermore some relations between the spaces (S) over cap (alpha)((p))[lambda,f] and (S) over cap (alpha)(lambda) are examined.
Keywords: Statistical convergence; almost convergence; Cesaro summability